Antimycotics suppress the Malassezia extract‐induced production of CXC chemokine ligand 10 in human keratinocytes. Issue 2 (February 2014) - Hau, Carren S.; Kanda, Naoko; Makimura, Koichi; Watanabe, Shinichi
Abstract Malassezia, a lipophilic yeast, exacerbates atopic dermatitis. Malassezia products can penetrate the disintegrated stratum corneum and encounter subcorneal keratinocytes in the skin of atopic dermatitis patients. Type 1 helper T (Th1) cells infiltrate chronic lesions with atopic dermatitis, and antimycotic agents improve its symptoms. We aimed to identify Malassezia‐induced chemokines in keratinocytes and examine whether antimycotics suppressed this induction. Normal human keratinocytes were incubated with a Malassezia restricta extract and antimycotics. Chemokine expression was analyzed by enzyme‐linked immunosorbent assays and real‐time polymerase chain reaction. Signal transducer and activator of transcription (STAT)1 activity was examined by luciferase assays. The tyrosine‐phosphorylation of STAT1 was analyzed by western blotting. The M. restricta extract increased the mRNA and protein expression of Th1‐attracting CXC chemokine ligand (CXCL)10 and STAT1 activity and phosphorylation in keratinocytes, which was suppressed by a Janus kinase inhibitor. The antimycotics itraconazole, ketoconazole, luliconazole, terbinafine, butenafine and amorolfine suppressed M. restricta extract‐induced CXCL10 mRNA and protein expression and STAT1 activity and phosphorylation. These effects were similarly induced by 15‐deoxy‐Δ‐12, 14‐prostaglandin J2 (15d‐PGJ2), a prostaglandin D2 metabolite. Antimycotics increased the release of 15d‐PGJ2 from keratinocytes. The antimycotic‐induced suppression of CXCL10 production and STAT1 activity was counteracted by a lipocalin‐type prostaglandin D synthase inhibitor. The antimycotics itraconazole, ketoconazole, luliconazole, terbinafine, butenafine and amorolfine may suppress the M. restricta‐induced production of CXCL10 by inhibiting STAT1 through an increase in 15d‐PGJ2 production in keratinocytes. These antimycotics may block the Th1‐mediated inflammation triggered by Malassezia in the chronic phase of atopic dermatitis.